(untitled) - Olueadamilare, Aina Ayyotunde (Cần Thơ, 2019)
This research is performed to investigate water quality in the shrimp culture areas of Soc Trang Province in order to provide a baseline for water quality management ensuring a sustainable shrimp culture in the area.
Keywords: Water quality,Chất lượng nước